How customer experience attributes influence customer satisfaction and online bank credibility - Loureiro, S. M. C.; Ferreira, E. S. (10th Annual Conference of the EuroMed-Academy-of-Business, 2017)
The banking sector has been focused its attention towards attracting Generation Upsilon since they have consolidated as a huge force with powerful spending power which will unavoidably rival with Baby Boomers' market dominance. Thus, this article analyses customer experience of Generation Upsilon and its effect on customer satisfaction and bank credibility. Empirical evidence, based on primary data from an online survey (550 questionnaires were spread over a two-month period in 2016 but only 205 were usable and completed) reveal that the customer experience attributes (mainly executional excellence and reputation) have a positive relationship on credibility and satisfaction. In addition, "Value for money", "Getting things right the first time" and "Put the consumer first" emerge as the most importance attributes for Generation Upsilon in experiencing the bank.